a) Use the formula for the sum of a geometric series to show that

$$\sum _{k=1}^n\:\left(z+z^2+\cdots+z^k\right)=\frac{nz}{1-z}-\frac{z^2}{\left(1-z\right)^2}\left(1-z^n\right),\:z\ne 1$$

I thought the formula for geometric series is $$\frac{a\left(1-r^n\right)}{1-r}=\frac{z\left(1-z^n\right)}{1-z}$$

How do I appraoch this?

b) Let $$z=\cos\left(\theta \right)+i\sin\left(\theta \right),\text{ where }0<\theta <2\pi.$$

By considering the imaginary part of the left-hand side of the equation of $a$, deduce that

$$\sum _{k=1}^n (\sin(\theta)+\sin(2\theta)+\cdots+\sin(k\theta ))=\frac{(n+1)\sin(\theta ) -\sin(n+1)\theta }{4\sin^2\left(\frac{\theta }{2}\right)}$$


$$\frac{z}{1-z}=\frac{i}{2\sin\left(\frac{\theta }{2}\right)} \left(\cos\left( \frac{\theta }{2} \right) +i\sin\left(\frac{\theta }{2}\right)\right)$$

  • $\begingroup$ I can tell you used software instead of writing the MathJax code by hand because it looked like something written by a lunatic. I've cleaned it up somewhat. $\endgroup$ Nov 9, 2014 at 1:42

2 Answers 2


This arabesque just might prove useful. $$\sum_{k=1}^n \sum_{j=1}^k x^j = \sum_{j=1}^n \sum_{k=j}^n x^j = \sum_{j=1}^n {{x^j - x^{n+1}\over 1 - x}}$$ Now resolve the remaining sum


$$\sum_{k=1}^n (z + z^2 + \cdots + z^k) = \sum_{k=1}^n z \frac{1 - z^k}{1-z} = \frac{z}{1-z} \sum_{k=1}^n ( 1 - z^k )$$

See where to go now?

  • $\begingroup$ I'm good, thanks $\endgroup$
    – user145591
    Nov 9, 2014 at 1:37

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.